PENGARUH BEBAS ONGKOS KIRIM, CASH ON DELIVERY DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT PEMBELIAN SECARA ONLINE - Sari, Gilang Ratna; Onsardi, Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to explain the effect of free shipping, cash on delivery and consumer trust on online purchasing intentions with a special study of Management Study Program students at the Faculty of Economics and Business, Bengkuu Muhammadiyah University. The method used is quantitative method and uses descriptive data analysis. The data analysis technique is a step that has been taken by the researcher. Sampling uses the Simple Random Sampling technique. to infer the meaning of the data that has been collected. This study uses multiple regression analysis. The results of research that has been done on the effect of Free Shipping, Cash On Delivery and Consumer Confidence on Buying Interest at Online Shops in Bengkulu City based on the correlation coefficient test obtained the value of R = 0.871 and the coefficient of determination R^2 = 0.758 value means that Free Shipping (X_1), Cash On delivery (X_2) and Consumer Trust (X3) contributed 0.758 or 75.8% to Purchase Interest (Y) at Online shops in Bengkulu City while the remaining 0.242 or 24.2% was influenced by variables others that were not included in this study. Keywords: Free Shipping, Cash on Delivery, Consumer Trust, purchase interest